Knowledge of graduated nursing students on breast feeding newborns with cleft lip and palate - João Lopes Toledo Neto; Carla Moretti de Souza; Edna Aparecida Lopes Bezerra Katakura; Talita Vidotte Costa; Kelly Holanda Prezotto; Thaís Bette Freitas (Rev Rene)
Objective: to identify the knowledge of nursing professionals about breastfeeding infants with a cleft lip and palate. Methods: a cross-sectional survey with nurses from two Brazilian Universities. A questionnaire with personal characteristics and knowledge related to nursing education was used. Results: all 13 nurses reported the lack of training on breastfeeding for infants with a cleft lip and palate. Most of the nurses were unaware of offering ways of feeding, suggesting that despite being one of the professionals who give more guidance on breastfeeding, knowledge on the subject is just beginning about the need for attention and care in attending children with a cleft lip and palate. Conclusion: further research in the area is recommended in order to improve understanding of caring for newborns with a cleft lip and palate, and to help professionals upgrade the care process.